2009
DOI: 10.1002/cbf.1593
|View full text |Cite
|
Sign up to set email alerts
|

Association of cholesteryl ester transfer protein −629C > A polymorphism with high‐density lipoprotein cholesterol levels in coronary artery disease patients

Abstract: In Turkish population, plasma HDL-C levels were found to be lower than in any other country and it is suggested that this is associated with genetic origin. The cholesteryl ester transfer protein (CETP) -629C > A polymorphism is associated with lower plasma CETP concentration, with increased HDL-C level. In the present study, the frequency of -629C > A polymorphism in patients with coronary artery disease (CAD) was investigated and the effect of genotype on HDL-C was evaluated in a Turkish population. For this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Both Taq1B and -629C > A polymorphisms could possibly have independent effects on HDL-C and apoA1 levels and hence they do not show significant effects individually when they are included in the same 2-way ANCOVA model. In the Turkish population, it was found that CETP - 629C  >  A polymorphism was not associated with CAD [43]. As with any complex traits, the genotypic effect is usually confounded by environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Both Taq1B and -629C > A polymorphisms could possibly have independent effects on HDL-C and apoA1 levels and hence they do not show significant effects individually when they are included in the same 2-way ANCOVA model. In the Turkish population, it was found that CETP - 629C  >  A polymorphism was not associated with CAD [43]. As with any complex traits, the genotypic effect is usually confounded by environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…CETP concentration is associated with the common Taq 1B polymorphism, and carriers of the B2 allele exhibit lower plasma CETP levels, higher HDL and reduced risk for coronary heart disease (Boekholdt et al, 2005;Thompson et al, 2008;Van Acker et al, 2008). However, other studies of different CETP polymorphisms, such as -629 C>A and Taq IB, did not support this association (Lu et al, 2003;Tanrikulu et al, 2009). Overall, the influence of CETP on the anti-atherogenic properties of HDL in vivo must be investigated.…”
Section: Discussionmentioning
confidence: 90%
“…Among these eligible studies, 33 involved the relationship between CETP rs708272 polymorphisms and CAD ( 15 47 ). Other 37 studied five other polymorphisms in the CETP gene, and 14 of them focused on rs5882 ( 15 , 22 , 26 , 29 , 31 , 32 , 35 , 44 , 46 , 50 , 53 , 55 , 59 , 60 ), 11 on rs1800775 ( 26 , 27 , 31 , 32 , 35 , 44 , 52 , 57 60 )3 on rs4783961 ( 16 , 35 , 51 ), 3 on rs247616 ( 19 , 48 , 56 ), 2 on rs5883 ( 49 , 54 ), 2 on rs1800776 ( 44 , 60 ), and 2 on rs1532624 ( 19 , 26 ). In addition, 6 studies deviated from HWE ( 19 , 30 , 32 , 39 , 41 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one articles mentioned studies performed among Caucasians ( 15 , 16 , 18 , 19 , 21 25 , 28 30 , 33 35 , 37 44 , 48 50 , 53 , 57 , 58 , 60 ), and 15 among Asians ( 17 , 20 , 26 , 27 , 31 , 32 , 36 , 45 , 46 , 51 , 52 , 54 56 , 59 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation